Evolução de células de pressão total e experiência da COPPE - Ribas, José Bonifácio Mader (1980)
A comprehensive study of design and performance of earth pressure cells as used in soils and rigid boundaries (diaphragm walls, sheet piling etc) was firstly done, and a general classification of these instruments was presented. It was sought to estabilish limiting values for the differents factors that influence the performance of these cells. An analysis of different installation procedures and how they influence the results was made. Researchers from COPPE/UFRJ have developed a few projects requiring field instrumentation. In two of these jobs, two types of earth pressure cells were installed in the excavations for the subway of Rio de Janeiro. The measurements are described. Also shown the calibration of one of the cell types. Finally, as a result of these studies, the Author designed a prototype of earth pressure cell. It is a confined fluid cell type, and its design avoids using foreign imported material. It is hoped that the development and calibration of this cell will permit to attain an improved design of earth pressure cell to be used in soil and rigid boundaries.